If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9.8m + -20 = -2m Reorder the terms: -20 + 9.8m = -2m Solving -20 + 9.8m = -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. -20 + 9.8m + 2m = -2m + 2m Combine like terms: 9.8m + 2m = 11.8m -20 + 11.8m = -2m + 2m Combine like terms: -2m + 2m = 0 -20 + 11.8m = 0 Add '20' to each side of the equation. -20 + 20 + 11.8m = 0 + 20 Combine like terms: -20 + 20 = 0 0 + 11.8m = 0 + 20 11.8m = 0 + 20 Combine like terms: 0 + 20 = 20 11.8m = 20 Divide each side by '11.8'. m = 1.694915254 Simplifying m = 1.694915254
| 11t-10=4t-5 | | 9.8m+20=2m | | 9.8m-10=m*5 | | 9.8-10=m*5m | | 9.8-10=m*5 | | 4u^2-6=5u | | 12x-8=4x+3 | | 9.8m-20=2m | | 3x+x=540 | | x^2+11x=15 | | 3x+y=540 | | 54-4x=23x+24 | | -103-7x=10+16 | | 6x+13=147-10x | | 6x+13=147-10 | | 2v^2+7v=-5 | | t+1+2+3+4+5+6+7+8+9=123456789 | | 114-6x=9x+4 | | 3x+9x+6x=396x | | -3x+(7ab-4)-5x-3b-(3a+22a-x)= | | 132-5x=31x+20 | | 13-8x=213-43x | | 2k+3= | | 41=15+13(9m-16) | | 41=15+13(19m-16) | | 2a+3=2a+4 | | log(x-2)+log(2-x)=1 | | 3lnx+ln(9-(8x^3))=0 | | 210S+265E=4485 | | 3lnx+ln(9-8x^3)=0 | | 3o+13=23-2o | | 15-(2x+3)=3-3X |